Socially responsible investing in the global market : the performance of US and European funds - Cortez, Maria do Céu (2012)
This paper investigates the style and performance of US and European global socially responsible funds. Several specifications of the return generating process are applied as well as their corresponding conditional versions. Most European global socially responsible funds do not show significant performance differences in relation to both conventional benchmarks and socially responsible benchmarks. US funds and Austrian funds show evidence of underperformance. By applying conditional models, we find evidence of time-varying betas, but not of time-varying alphas. With respect to investment style, we find evidence that socially responsible funds are strongly exposed to small cap and growth stocks. While these results are consistent with previous studies, they uncover some misclassification issues in these funds. Finally, we also document a significant home bias for global socially responsible funds.